2021
DOI: 10.1016/j.celrep.2021.110148
|View full text |Cite
|
Sign up to set email alerts
|

The microglial P2Y6 receptor mediates neuronal loss and memory deficits in neurodegeneration

Abstract: Highlights d P2Y 6 R knockout prevents microglial phagocytosis of stressed-but-viable cells d P2Y 6 R knockout does not alter microglial phagocytosis of healthy or dead cells d P2Y 6 R knockout prevents microglial phagocytosis of neurons induced by Ab in vivo d P2Y 6 R knockout reduces neuronal loss and memory deficits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…Additionally, P2Y6R-mediated phagocytosis mediates the removal of neuronal debris in a cerebral stroke model [397]. Although these findings demonstrate the protective role of P2Y6R, microglial phagocytosis response induced by this receptor has been shown to exacerbate AD pathology by promoting microglial phagocytosis of stressed but viable neurons, which are capable of releasing UDP [398]. In mixed neuron/glia culture, the use of the P2Y6R antagonist MRS2578 delayed the neuronal loss induced by Aβ, and this effect was mediated by inhibiting microglial phagocytosis response.…”
Section: P2y Receptorsmentioning
confidence: 87%
“…Additionally, P2Y6R-mediated phagocytosis mediates the removal of neuronal debris in a cerebral stroke model [397]. Although these findings demonstrate the protective role of P2Y6R, microglial phagocytosis response induced by this receptor has been shown to exacerbate AD pathology by promoting microglial phagocytosis of stressed but viable neurons, which are capable of releasing UDP [398]. In mixed neuron/glia culture, the use of the P2Y6R antagonist MRS2578 delayed the neuronal loss induced by Aβ, and this effect was mediated by inhibiting microglial phagocytosis response.…”
Section: P2y Receptorsmentioning
confidence: 87%
“…We also found that injection of amyloid beta into the brains of mice induced microglial phagocytosis of neurons, loss of neurons, and memory deficits, all of which were prevented in P2Y6R knockout mice [26]. Similarly, we used a chronic model of neurodegeneration (i.e., mice expressing P301S TAU) and found that crossing these mice with P2Y6R knockout mice prevented the brain neuronal loss and memory deficits [26]. Thus, we were interested to know whether P2Y6R knockout could prevent the loss of peri-infarct neurons after transient brain ischemia.…”
Section: Resultsmentioning
confidence: 65%
“…More recently, we showed that chronic, peripheral LPS induced neuronal loss in the brains of mice and this neuronal loss was prevented by knockout of P2Y6R [25]. We also found that injection of amyloid beta into the brains of mice induced microglial phagocytosis of neurons, loss of neurons, and memory deficits, all of which were prevented in P2Y6R knockout mice [26]. Similarly, we used a chronic model of neurodegeneration (i.e., mice expressing P301S TAU) and found that crossing these mice with P2Y6R knockout mice prevented the brain neuronal loss and memory deficits [26].…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations